Wastewater treatment of a municipal slaughterhouse in the city of Tacna-Peru using an upflow anaerobic sludge blanket reactor - Gonzales-Condori, Elvis Gilmar (2024)
The present research study was carried out at the Mario Eyzaguirre municipal slaughterhouse in the city of Tacna, Peru where the design, construction, and evaluation of a water treatment system comprising catchment units, a desander, a settling tank, a grease trap, and an Upflow Anaerobic Sludge Blanket (UASB) was proposed. The initial and final values of BOD5, COD, ammoniacal nitrogen, oils and fats, pH, total dissolved solids, and total dissolved solids were used as indicators of treatment efficiency. The results show a percentage of removal at a temperature of 20°C of 36 % of COD and 35 % of BOD, and the results for temperature values at 35°C showed improvements in the removal of organic pollutants with an average value of 54 % for BOD5 and 45 % for COD. To improve the study proposal, units such as coagulation, flocculation, filtration, and disinfection were complemented and installed after the UASB, where the results indicate improvements in water quality up to 70.84 % for BOD5 and 70.69 % for COD. The present study demonstrates that applying a UASB in a municipal animal feedlot can considerably reduce the pollution of its effluents.